2003
DOI: 10.1083/jcb.200303131
|View full text |Cite
|
Sign up to set email alerts
|

Clustering of multiple specific genes and gene-rich R-bands around SC-35 domains

Abstract: Typically, eukaryotic nuclei contain 10–30 prominent domains (referred to here as SC-35 domains) that are concentrated in mRNA metabolic factors. Here, we show that multiple specific genes cluster around a common SC-35 domain, which contains multiple mRNAs. Nonsyntenic genes are capable of associating with a common domain, but domain “choice” appears random, even for two coordinately expressed genes. Active genes widely separated on different chromosome arms associate with the same domain frequently, assorting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
182
1
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 191 publications
(207 citation statements)
references
References 41 publications
(77 reference statements)
18
182
1
1
Order By: Relevance
“…The genes are found outside of the XIST RNA (yellow), which extends beyond the Barr body, the visible manifestation of the heterochromatin. 49,50,58,59) and splicing and transcription factors localize (22,49,51,60,61). The act of silencing and condensing the inner core of Xi may make the existing concentration of protein-coding genes in the peripheral region more pronounced and observable.…”
Section: Discussionmentioning
confidence: 99%
“…The genes are found outside of the XIST RNA (yellow), which extends beyond the Barr body, the visible manifestation of the heterochromatin. 49,50,58,59) and splicing and transcription factors localize (22,49,51,60,61). The act of silencing and condensing the inner core of Xi may make the existing concentration of protein-coding genes in the peripheral region more pronounced and observable.…”
Section: Discussionmentioning
confidence: 99%
“…Support for this was shown in live mammalian nuclei where one or more speckles was shown to provide splicing factors to the inducible BK virus and cytomegalovirus immediate early transcripts stably integrated into the baby hamster or rat genomes, respectively (Misteli et al, 1997). More recently, Shopland et al (2003) reported that multiple specific genes and gene-rich R-bands cluster around SC35 domains (speckles) and proposed that the speckles are functional centers for a multitude of clustered genes or local euchromatic neighborhoods.…”
Section: The Organization and Dynamics Of Plant Sr Proteins Are Depenmentioning
confidence: 98%
“…They may involve differences between human and rodent nuclear organization. We next sought to analyze whether expressed gene loci colocalize with nuclear splicing factor speckles, as it was observed for several active genes (Nielsen et al 2002;Shopland et al 2003;Chuang et al 2006;Takizawa et al 2008). We codetected splicing speckles together with the oct3/4 gene locus in undifferentiated ES cells, in ES cells after 5 days of differentiation, and in terminally differentiated, postmitotic macrophages.…”
Section: Gene Positioning and Expressionmentioning
confidence: 99%